2002
DOI: 10.1086/342519
|View full text |Cite
|
Sign up to set email alerts
|

Population Differentiation and Natural Selection for Water‐Use Efficiency inImpatiens capensis(Balsaminaceae)

Abstract: In xeric environments, water-use efficiency (WUE) is likely to be a target of natural selection. Higher WUE is expected to confer a fitness advantage in drought conditions, but this prediction has rarely been tested. To examine the relationships between WUE and fitness, two common garden experiments were conducted. Inbred lines of Impatiens capensis derived from wet and relatively dry sites were planted into dry field conditions in an open and a woodland site. The lines from the dry population increased their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
180
3
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(196 citation statements)
references
References 37 publications
8
180
3
1
Order By: Relevance
“…In addition, higher A max may have been maladaptive or adaptively neutral (Tables 4, 5) because increased RuBP regeneration capacity is metabolically wasteful, especially when plants are operating at low C i because of stomatal closure (Sage 1994). In contrast to previous work (Dudley 1996;Heschel et al 2002Heschel et al , 2004Heschel and Riginos 2005), we found that lower g s , and therefore increased water conservation (Ehleringer 1993) was not adaptive in the dry environment for L. cardinalis. Instead, plasticity of g s was adaptive in L. cardinalis because plants with higher g s had higher fitness within the wet treatment (Table 5).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In addition, higher A max may have been maladaptive or adaptively neutral (Tables 4, 5) because increased RuBP regeneration capacity is metabolically wasteful, especially when plants are operating at low C i because of stomatal closure (Sage 1994). In contrast to previous work (Dudley 1996;Heschel et al 2002Heschel et al , 2004Heschel and Riginos 2005), we found that lower g s , and therefore increased water conservation (Ehleringer 1993) was not adaptive in the dry environment for L. cardinalis. Instead, plasticity of g s was adaptive in L. cardinalis because plants with higher g s had higher fitness within the wet treatment (Table 5).…”
Section: Discussioncontrasting
confidence: 90%
“…Moreover, the available evidence suggests that plastic physiological responses occurring through both mechanisms can be adaptive or maladaptive in plants, depending on the ecological context. For example, stomatal closure under drought can be adaptive because of increased water con-servation (Ehleringer 1993;Dudley 1996;Heschel et al 2002Heschel et al , 2004 or maladaptive because of associated reductions in photosynthetic rate (Arntz et al 1998). Similarly, increased photosynthetic capacity through the up-regulation of ribulose-1,5-bisphosphate (RuBP) carboxylase/oxygenase (Rubisco) activity could allow plants to maintain relatively high instantaneous photosynthetic rate despite decreased C i (Anderson et al 2001).…”
mentioning
confidence: 99%
“…The increased instantaneous water use efficiency confers a fitness advantage under stressful conditions in the field (Heschel et al 2002) and thus might increase the survival of tree species. The application of hydrogels leads to a significant reduction in the Vol.…”
Section: Resultsmentioning
confidence: 99%
“…The two focal regions for candidate gene method validation are highlighted in green. (Heschel et al, 2002;Blum, 2005;Schmalenbach et al, 2014). By contrast, TSU originates from Southwestern Japan, where more mesic growing season conditions exist.…”
Section: Genetic Correlations Underlie Pleiotropic Qtlsmentioning
confidence: 98%
“…For example, mild early season drought may simultaneously select for cellular dehydration avoidance through stomatal closure (Heschel et al, 2002) and reduced growth rates (Schmalenbach et al, 2014). Alternatively, strong late season drought may select for drought escape through early flowering and fast growth while soil water conditions are favorable (Meyre et al, 2001;Heschel and Riginos, 2005;Sherrard and Maherali, 2006).…”
Section: Genetic Correlations Underlie Pleiotropic Qtlsmentioning
confidence: 99%